Clinical Pathway for Management of Suspected or Positive Novel Coronavirus-19 Patients With ST-Segment Elevation Myocardial Infarction. Issue 2 (June 2020) - Ranard, Lauren S.; Ahmad, Yousif; Masoumi, Amirali; Chuich, Taylor; Romney, Marie-Laure S.; Gavin, Nicholas; Sayan, Osman R.; Kirtane, Ajay J.; Rabbani, LeRoy E.
Abstract : Novel coronavirus-19 disease (COVID-19) is an escalating, highly infectious global pandemic that is quickly overwhelming healthcare systems. This has implications on standard cardiac care for ST-elevation myocardial infarctions (STEMIs). In the setting of anticipated resource scarcity in the future, we are forced to reconsider fibrinolytic therapy in our management algorithms. We encourage clinicians to maintain a high level of suspicion for STEMI mimics, such as myopericarditis which is a known, not infrequent, complication of COVID-19 disease. Herein, we present a pathway developed by a multidisciplinary panel of stakeholders at NewYork-Presbyterian/Columbia University Irving Medical Center for the management of STEMI in suspected or confirmed COVID-19 patients.